ROSA: An Andean Network of Social–Ecological Observatories - Carilla, Julieta (2024)
We present the Andean Social–Ecological Observatory Network (ROSA, for Red de Observatorios Socioecologicos Andinos), a continent-wide monitoring initiative established to address major challenges in the management of knowledge on social–ecological systems (SES) in the Andes. The Andes, the longest mountain chain in the world, provide key ecosystem services for human wellbeing across the continent. However, the region faces multiple impacts associated with climate change and land-use change related to demographic transitions, and thus long-term monitoring is key for developing adaptation strategies to this environmental change. ROSA constitutes a bottom-up initiative to systematize and integrate social and ecological monitoring efforts into observatories, and to do so under a coproduced framework that fosters science–policy dialogue and promotes sustainable land management. The main research questions addressed by these social–ecological observatories include understanding how distant and proximate drivers of change interact with local social, cultural, economic, and environmental contexts to influence the functioning of different SES in the Andes at multiple spatial and temporal scales. We describe the origins, structure, objectives, and strategies of ROSA and key challenges faced by different monitoring networks working in the region with regard to data generation and knowledge transfer. Currently, ROSA consists of 8 nodal observatories, comprising more than 50 monitoring initiatives focused on hydroclimate, ecological, and land-use dimensions. The bottom-up structure of ROSA is founded on proven expertise in long-term data gathering and analyses and on the strong commitment of nodal monitoring groups. Effective codesign and participatory monitoring are being developed so that ROSA can contribute to knowledge coproduction for sustainable land management.